2021
DOI: 10.17843/rpmesp.2021.384.7776
|View full text |Cite
|
Sign up to set email alerts
|

Intercambio desde los cigarrillos convencionales a los sistemas electrónicos de administración de nicotina: revisión sistemática rápida con metaanálisis y aspectos económicos

Abstract: Objetivos. Evaluar cómo y en qué medida se produce un intercambio desde los cigarrillos convencionales (CC) a los sistemas electrónicos de administración de nicotina (SEAN). Materiales y métodos. Se realizó una revisión sistemática hasta agosto de 2019. El desenlace primario fue la proporción de un intercambio completo o parcial de CC a los SEAN y sus aspectos económicos. Los desenlaces secundarios como medidas de resultado fueron la probabilidad de intercambio y la tendencia en el intercambio por países. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
0
5
0
1
Order By: Relevance
“…However, it is now known that the substances that CDC associated with lung injury are not the only ones related to endothelial dysfunction 13 14 15 . A recent study demonstrated that the main component of e-cigarettes, glycerol, increases neutrophil migration and fibrosis in endotoxin-induced lung injury through activation of p38 mitogen-activated protein kinase 16 .…”
Section: Antecedents and Etiologymentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is now known that the substances that CDC associated with lung injury are not the only ones related to endothelial dysfunction 13 14 15 . A recent study demonstrated that the main component of e-cigarettes, glycerol, increases neutrophil migration and fibrosis in endotoxin-induced lung injury through activation of p38 mitogen-activated protein kinase 16 .…”
Section: Antecedents and Etiologymentioning
confidence: 99%
“…A histological study found that when buccal cells are exposed to the liquid-based component of vaporizers, marked cellular alterations occur, including apoptosis, dyskeratosis, and epithelial atrophy 14 . In vitro studies have demonstrated a dose-dependent decrease in the viability of normal human bronchial epithelial bronchial cells after exposure to vapor from electronic vape devices 14 15 . DNA damage also appears to be dose-dependent, in addition there is a depletion of glutathione stores and an increase in cell membrane permeability 19 .…”
Section: Antecedents and Etiologymentioning
confidence: 99%
See 3 more Smart Citations